Pelunasan Hutang Terhadap Jaminan Fidusia - Adawiyah Nasution (Universitas Islam Sumatera Utara, 2018)
Abstract ASEAN Economic Community to create a highly competitive single production-based market to promote equitable economic development for all member countries and to integrate them with the global community; consequently the impact will make the competition in every field increasingly tight, including in education. To achieve the target as members of ASEAN Economic Community, it is obligatory for them to increase the adequate human resources and to be daring in ASEAN free market competition. Then, a question